2021
DOI: 10.3390/microorganisms9020291
|View full text |Cite
|
Sign up to set email alerts
|

Legionellosis Caused by Non-Legionella pneumophila Species, with a Focus on Legionella longbeachae

Abstract: Although known as causes of community-acquired pneumonia and Pontiac fever, the global burden of infection caused by Legionella species other than Legionella pneumophila is under-recognised. Non-L. pneumophila legionellae have a worldwide distribution, although common testing strategies for legionellosis favour detection of L. pneumophila over other Legionella species, leading to an inherent diagnostic bias and under-detection of cases. When systematically tested for in Australia and New Zealand, L. longbeacha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 137 publications
0
44
0
1
Order By: Relevance
“…Even if L. pneumophila is responsible for most legionellosis outbreaks, L. non- pneumophila (Lnp) strains are also involved in legionellosis cases, and often their responsibility is under-recognized due to diagnostic bias [ 2 , 39 , 46 ]. Even though it is now well-known that among the approximately 60 species of Legionella, 50% are able to infect humans [ 47 ], the responsibility for 4% of legionellosis cases can still not be attributed to a known species [ 39 ]. An extensive detection of Lnp strains in water distribution systems demonstrated that 16% of the sampled water was contaminated with Legionella , and that Lnp strains were prevalent [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if L. pneumophila is responsible for most legionellosis outbreaks, L. non- pneumophila (Lnp) strains are also involved in legionellosis cases, and often their responsibility is under-recognized due to diagnostic bias [ 2 , 39 , 46 ]. Even though it is now well-known that among the approximately 60 species of Legionella, 50% are able to infect humans [ 47 ], the responsibility for 4% of legionellosis cases can still not be attributed to a known species [ 39 ]. An extensive detection of Lnp strains in water distribution systems demonstrated that 16% of the sampled water was contaminated with Legionella , and that Lnp strains were prevalent [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The result of a positive PCR test will be designated as a probable case, but not as a confirmed case [ 36 ]. Many studies demonstrate that legionellosis cases were related to Legionella non- pneumophila (Lnp) strains and that these strains are frequently isolated in the environment [ 2 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ]. For example, Steege and Moore detected by means of qPCR on the mip gene the presence of Legionella in 95% of samples, but L. pneumophila was only detected in 1.8% of samples [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, it is not possible to distinguish Legionnaires’ disease from other forms of pneumonia. Therefore, a proper diagnostic method that enables early identification of Legionella species is critical in the management of patients, as a delay in the provision of an effective treatment against Legionella could increase morbidity and mortality, especially in immunosuppressed patients ( Ruiz et al, 2000 ; Pedro-Botet and Yu, 2006 ; Soler-Majoral et al, 2016 ; Chambers et al, 2021 ). Nowadays, Legionnaires’ disease diagnosis almost exclusively depends on urinary antigen tests, representing 82 and 97% of Legionnaires’ disease confirmation in Europe and the United States, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account its environmental presence, the lack of any reported case could be due to the fact that the diagnostic methods most commonly used in hospitals to confirm cases of Legionnaires’ disease (immunochromatography and ELISA) only detect the L. pneumophila serogroup 1 ( Muder and Yu, 2002 ; Blyth et al, 2009 ). Thus, infections caused by L. feeleii or other species of non- L egionella pneumophila are not detected ( Muder and Yu, 2002 ; Svarrer et al, 2012 ; Vaccaro et al, 2016 ; Chambers et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation